Chronicle of a death foretold - Garcia Marquez, Gabriel, 1928-; Rabassa, Gregory; Penguin Books (London : Penguin Books, 1996)
Studies a murder which takes place shortly after a wedding and explores the mass community complicity that allowed it to happen.
Keywords: Fiction, Spanish -- Translation into English; Murder -- Fiction